No DDRama at chromosome ends: TRF2 takes centre stage - Feuerhahn, Sascha; Chen, Liuh-yow; Luke, Brian; Porro, Antonio (Trends in biochemical sciences, 2015)
Telomeres are nucleoprotein structures capping the natural termini of eukaryotic linear chromosomes. Telomeres possess an inherent ability to circumvent the activation of a full-blown DNA damage response (DDR), and hence fusion reactions, by limiting inappropriate double-strand break (DSB) repair and processing activities at eukaryotic chromosome ends. A telomere-specific protein complex, termed shelterin, has a crucial function in safeguarding and securing telomere integrity. Within this complex, TRF2 has emerged as the key player, dictating different states of telomere protection during the replicative lifespan of a cell. How TRF2 prevents activation of DSB repair activities at functional telomeres has now been extensively investigated. In this review we aim at exploring the complex and multi-faceted mechanisms underlying the TRF2-mediated protection of eukaryotic chromosome ends.
Gesehen am 17.11.2020